The boatswain's manual - McLeod, William A. (Brown, Son & Ferguson, 2006)
These pages have been compiled as a book of elementary knowledge for the beginner and also as a reference-book for older deck ratings, especially those who seek information relating to everyday seamanship problems, or who wish to prepare for the qualifying examination for the Certificate of Qualification as Efficient Deck Hand (E.D.H.)